There's a place for us? The Digital Agenda Committee and internet policy in the German Bundestag - Julia Schwanholz; Tobias Jakobi (Internet Policy Review, 2020)
The Digital Agenda Committee of the Bundestag was a remarkable institutional change in Germany. It represents the first body of its kind among all EU member states. In this article, we analyse it in its first legislative session (2013-2017) and examine the case of data retention legislation to determine if it had the effect sought by internet policy entrepreneurs of the time. Thereby, we contribute to a better understanding of whether internet issues became institutionalised in the Bundestag and, generally, how new policies emerge. Our results show that the new committee did not promote and share a common policy image in the first session. However, it strongly drifted to become a venue for digital policy. International scholars can learn not only about the establishment of new committees in the German parliament but also about an analytical framework to analyse cases in other parliaments or institutional settings.
Keywords: 300; Bundestag; Data retention; Digital Agenda Committee; Discourse network analysis; Internet policy